Tantangan Klausul Akad Syirkah Di Indonesia - Abdul Mughni; Kokoh Hamdani (Jurnal Hukum Ekonomi Syariah, 2020)
Syirkah al musahamah is a contemporary contract which is the development of classical syirkah. It has been formulated by the previous madzhab priests. Syirkah al musahamah developed by contemporary scholars (Ulama) to answer the problems of business that occur in the modern era, such as intercompany cooperation, Limited liability company (PT), CV, and others. Basically, implementation is inseparable from the basic syirkah, in order to remain in the scope of the Shariah and become a halal company. Implementation of Syirkah Al Musahamah on syariah cooperative 212 is globally in two of business units : Application of syirkah al musahamah contract on sharia cooperative 212. The members provide principal savings and mandatory savings. In other words, deposits become the shares they have in a sharia cooperative 212 which is managed using a syirkah al musahamah Implementation on the business unit of cooperative sharia 212. The members of cooperatives could be participate in the development of retail business by buying shares of cooperative sharia 212. Scholars (Ulama) have differences of opinion on the law syirkah al musahamah on the object traded and the implementation of pillars syirkah.